Motivasi Penyandang Disabilitas Netra Dalam Upaya Mengembangkan Kemandirian di Yayasan Netra Mandiri Palembang - Utami, Amelia; Utami, Fajar Tri (Indonesian Journal of Behavioral Studies, 2023)
This study aims to describe Motivation of Blindness People on Their Efforts to Develop Autonomy at Yayasan Netra Mandiri Palembang. This study used descriptive qualitative methods. The technique of selecting the subjects used purposive sampling and there are three selected subjects. Methods of data collection used interview, observation and documentation. The results of this study describes motivation of the three subjects in an effort to develop autonomy, which is oriented about condition to ensure that their desire to be seen as independent and equal just like normal people, and motivation to fulfill the basic needs of daily life, fulfill the need to growth, develop and become an independent blind especially on economic. Encouragement to be accepted and appreciated while around Yayasan; home and encouragement to socialize to normal people as well as other blind people. The methods and efforts of the three subjects to develop autonomy were participating in the training held by Yayasan Netra Mandiri Palembang. The difference between three subjects is the type of training that is taken because it depends to each interests and talents.